Autocrine Action of Thrombospondin-2 Determines the Chondrogenic Differentiation Potential and Suppresses Hypertrophic Maturation of Human Umbilical Cord Blood-Derived Mesenchymal Stem Cells. (25th August 2015) - Jeong, Sang Young; Ha, Jueun; Lee, Miyoung; Jin, Hye Jin; Kim, Dong Hyun; Choi, Soo Jin; Oh, Wonil; Yang, Yoon Sun; Kim, Jae-Sung; Kim, Byung-Gyu; Chang, Jeong Ho; Cho, Dong-Hyung; et al.
Abstract: Previous studies have shown that mesenchymal stem cell (MSC)-based therapies have varying efficacies for the treatment of various diseases, including cartilage defects. In this study, we demonstrated that the chondrogenic differentiation potential of human umbilical cord blood-derived MSCs (hUCB-MSCs) obtained from different individual donors varies, and we investigated the molecular basis for this variation. Microarray gene expression analysis identified thrombospondin-2 ( TSP2 ) as a candidate gene underlying the interindividual variation in the chondrogenic differentiation potential of hUCB-MSCs. To assess the association between TSP-2 and the differentiation potential, we evaluated chondrogenic differentiation of hUCB-MSCs treated with TSP2 siRNA. In addition, we studied the effect of supplementing exogenous recombinant TSP-2 on TSP2 siRNA-treated hUCB-MSCs. We found that TSP-2 autocrinally promoted chondrogenic differentiation of hUCB-MSCs via the Notch signaling pathway, which was confirmed in MSCs from other sources such as bone marrow and adipose tissue. Interestingly, we observed that TSP-2 attenuated hypertrophy, which inevitably occurs during chondrogenic differentiation of hUCB-MSCs. Our findings indicated that the variable chondrogenic differentiation potential of MSCs obtained from different donors is influenced by the TSP-2 level in the differentiating cells. Thus, the TSP-2 level can be used as a marker to select MSCs with superior chondrogenic differentiation potential for use in cartilage regeneration therapy. Stem Cells 2015;33:3291–3303